Cultural and International Dissonance on Girls Empowerment: the Case of Afghanistan’s Female Son - Made Yaya Sawitri (President University, 2017)
Bacha Posh is a Dari term which literary means “girls dressed as boys. Girls who were born in a family without son must disguise themselves as boys under social or economic pressure. This arrangement end when the girl reaches puberty as she has to turn back to her birth gender and get married. This article underlines incongruence between international discourse and cultural discourse on girl child. International community often depicts girl child as helpless population with very limited capacity and agency. Bacha Posh is proving just the opposite. They serve as a portrayal of Afghan girls who cleverly resisting the rigid societal norms in the fragile country where having sons equal security. Through the lives of the bacha posh, this article wishes to unveil what it means to be girls in the post-war Afghanistan where the international community has persistently been trying to teach Afghans about gender and human rights.